The Influnce E-Commerce Shopee Strategic Online Purchasing Decision Generation Z in Panam Pekanbaru - Ermansyah, Ermansyah (InJEBA : International Journal of Economics, Business and Accounting, 2024)
E-Commerce competition is becoming increasingly attractive in the world of online shopping, it requires a special strategy in order to compete competitively, E Commerce Shoope performs a Twin Date Event Strategy, Flash Sale, and Free Shipping Cost, Population in this study amounts to 100 people using purposive sampling methods. Based on the results of this study, Twins Date Events, Flash Sale and Free Shipping have influenced purchasing decisions both partially and simultaneously. The results of the Determination Coefficient show that the magnitude of the influence of both free variables together on the bound variable is 54.7% and the remaining 45.3% is another variable not studied. Future research could delve into these unexplored variables to provide a more comprehensive understanding of what drives purchasing decisions in the e-commerce sector. Understanding these additional factors could further assist e-commerce platforms like Shoope in refining their marketing strategies, ensuring they not only attract but also retain customers in a highly competitive market.